Implementation of Pancasila Student Profiles on Protista Material using Wizer. Me Application - Putri, Rossanita Truelovin Hadi; Sholihah, Fatikhatun Nikmatus; Huda, Moch. Faizul (Jurnal Pendidikan MIPA, 2023)
Abstract: The Pancasila student profile is a character value and competency that is the goal of students by implementing the noble values of Pancasila. Implementing the Pancasila student profile is necessary to develop the student's character, which is starting to decline. This research aims to describe the implementation of the Pancasila student profile on protist material with the help of the Wizer.me application. The subjects in this research were 36 students from SMA Negeri 3 Mojokerto. This type of research is descriptive qualitative, and data collection is carried out using interviews, observation, and documentation techniques. The results of this research are that the Pancasila student profile has been implemented in schools very well. Teachers and students have been directed in learning the Merdeka Curriculum so that implementing the Pancasila student profile in each critical dimension, creative dimension, dimension of being devoted to God Almighty and having noble morals, dimensions of cooperation, and independence obtains satisfactory results. The Wizer.me application as a learning tool on protist material can be a fun, innovative, and effective learning reference. Keywords: pancasila student profile, protist, wizer.me. Abstrak: Profil pelajar Pancasila merupakan suatu nilai karakter serta kompetensi yang menjadi tujuan peserta didik dengan mengimplementasikan nilai-nilai luhur Pancasila. Urgensi penerapan profil pelajar Pancasila diperlukan bagi perkembangan karakter peserta didik yang mulai menurun. Tujuan dari penelitian ini ialah untuk mendeskripsikan implementasi profil pelajar Pancasila pada materi protista dengan berbantuan aplikasi wizer.me. Subjek pada penelitian ini ialah peserta didik dari SMA Negeri 3 Kota Mojokerto sebanyak 36 orang. Jenis penelitian dengan deskriptif kualitatif serta pengumpulan data yang dilakukan mengunakan teknik wawancara, observasi dan dokumentasi. Hasil dalam penelitian ini ialah implementasi profil pelajar Pancasila telah diterapkan di sekolah dengan sangat baik. Guru serta peserta didik sudah diarahkan dalam pembelajaran Kurikulum Merdeka, sehingga implementasi profil pelajar Pancasila pada tiap dimensi kritis, dimensi kreatif, dimensi bertakwa kepada Tuhan Yang Maha Esa dan berakhlak mulia, dimensi bergotong royong dan mandiri memperoleh hasil yang memuaskan. Aplikasi wizer.me sebagai sarana pembelajaran pada materi protista dapat menjadi referensi pembelajaran yang menyenangkan, inovatif, dan efektif.  Kata kunci: profil pelajar pancasila, protista, wizer.me. DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp730-741